DETERMINAN FRAUD DANA DESA: PENGUJIAN ELEMEN FRAUD HEXAGON - Ari, Utami Avista Dwi; Inapty, Biana Adha; Waskito, Iman (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
This study aims to determine the effect of hexagon fraud namely pressure, opportunity, rationalization, competence, arrogance, and collusion on village fund fraud in villages in Jonggat District. This type of research is quantitative research with an associative approach. This study uses primary data obtained by distributing questionnaires to respondents directly. The population in this study were village officials who worked in the village office environment in the Jonggat sub-district by using a purposive sampling technique to determine the sample. The analytical tool used in this study is software SmartPLS (Partial Least Square) version 3.0. The results of this study indicate that opportunity, rationalization, arrogance, and collusion have a positive and significant effect on the fraud of village funds in villages in Jonggat District. Meanwhile, the variables of pressure and competence do not affect the fraud of village funds. The results of this study can be used as reference material for further research on fraud and this research can be used by parties who have an interest in village fund management to make policies to prevent fraud in managing village funds